2022
DOI: 10.3390/ijms23031436
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of RADA16-I and CDNF on Neurogenesis and Neuroprotection in Brain Ischemia-Reperfusion Injury

Abstract: Scaffold materials, neurotrophic factors, and seed cells are three elements of neural tissue engineering. As well-known self-assembling peptide-based hydrogels, RADA16-I and modified peptides are attractive matrices for neural tissue engineering. In addition to its neuroprotective effects, cerebral dopamine neurotrophic factor (CDNF) has been reported to promote the proliferation, migration, and differentiation of neural stem cells (NSCs). However, the role of RADA16-I combined with CDNF on NSCs remains unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Moreover recently RADA16-I peptide was studied as a artificial ECM for studying cancer cell behaviours 29 . Delivery of an unmodified RADA16-I hydrogel results in immediate hemostasis, which has been proven by its application on cut wounds on the brain, liver, femoral artery, spinal cord, skin and ischemia–reperfusion injury 30 33 . The results showed that RADA16-I alone slightly increased wound closure and reepithelization compared to the control.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover recently RADA16-I peptide was studied as a artificial ECM for studying cancer cell behaviours 29 . Delivery of an unmodified RADA16-I hydrogel results in immediate hemostasis, which has been proven by its application on cut wounds on the brain, liver, femoral artery, spinal cord, skin and ischemia–reperfusion injury 30 33 . The results showed that RADA16-I alone slightly increased wound closure and reepithelization compared to the control.…”
Section: Introductionmentioning
confidence: 99%
“…Like neurotrophic factors, glial cell line-derived neurotrophic factor (GDNF) has a chemoattractant effect in the migration of neuronal precursor cells along the rostral migratory stream [ 42 ]. Furthermore, for non-classical neurotrophic factors, mesencephalic astrocyte-derived neurotrophic factor (MANF), together with its homolog cerebral dopamine neurotrophic factor (CDNF), can promote the migration of neural progenitor cells in the stroke model [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophic factors may also be pivotal elements of neuronal regeneration and neuroprotection. Hydrogel carried with BDNF, and cerebral dopamine neurotrophic factor (CDNF) exerts therapeutic effects on stroke models of rats ( Ravina et al, 2018 ; Liu X. et al, 2022 ). In addition to the common factors, erythropoietin (EPO) also plays a fundamental role in neural development and neuroprotection ( Wakhloo et al, 2020 ).…”
Section: Neurorestorative and Neuroprotective Mechanism Of Biomaterialsmentioning
confidence: 99%